In situ electrochemical synthesis of polypyrrole Cu2O MoO3 nanocomposite on graphene oxide nanosheets for hydrogen generation and supercapacitors - Reza Dadashi; Morteza Bahram; Khalil Farhadi (Scientific Reports)
Abstract In this work, a simple, single-step electrochemical method is used to decorate a ternary Polypyrrole-Cu2O-MoO3 (PPy-Cu2O-MoO3) nanocomposite on Graphene Oxide (GO) nanosheets formed on a Graphite Foil Electrode (GFE). The characterization confirmed successful synthesis of ternary nanocomposite, and electrochemical tests showed the electrode performed well as both a supercapacitor and a hydrogen evolution reaction (HER). The investigation of the hydrogen production reaction by the PPy-Cu2O-MoO3/GO/GFE shows that this electrode has a smaller Tafel slope and overpotential. Additionally, the PPy-Cu2O-MoO3/GO/GFE has a specific capacitance of 1010.30 mF cm−2 at 1 mA cm−2 in a 0.5 M H2SO4 electrolyte solution. The evaluation of the fabrication of a symmetric solid-state supercapacitor device shows that the constructed device has an excellent capacitance of 596.5 mF cm−2 at 1 mA cm−2 and a cyclic stability of 82.4% after 6000 GCD cycles. For hydrogen evolution reaction, the electrode demonstrated an overpotential of 361 mV at 10 mA cm−2 and a Tafel slope of 142 mV dec−1, indicating favorable electrocatalytic activity. These results highlight the potential of the synthesized nanocomposite as a multifunctional electrode material for both energy storage and clean energy production.